Segmentation of the mouse hippocampal formation in magnetic resonance images - Richards, K.; Watson, Charles; Buckley, R.; Kurniawan, N.; Yang, Z.; Keller, M.; Beare, R.; Bartlett, P.; Egan, G.; Galloway, G.; Paxinos, G.; Petrou, S.; et al. (Academic Press, 2011)
The hippocampal formation plays an important role in cognition, spatial navigation, learning, and memory. High resolution magnetic resonance (MR) imaging makes it possible to study in vivo changes in the hippocampus over time and is useful for comparing hippocampal volume and structure in wild type and mutant mice. Such comparisons demand a reliable way to segment the hippocampal formation. We have developed a method for the systematic segmentation of the hippocampal formation using the perfusion-fixed C57BL/6 mouse brain for application in longitudinal and comparative studies. Our aim was to develop a guide for segmenting over 40 structures in an adult mouse brain using 30 μm isotropic resolution images acquired with a 16.4 T MR imaging system and combined using super-resolution reconstruction.